Le Corbusier and the maisons Jaoul - Maniaque Benton, Caroline; Le Corbusier, 1887-1965. (New York : Princeton Architectural Press, 2009)
Presents a detailed examination of these lesser-known, yet architecturally-significant of Le Corbusier's houses, which encompassed four years of intense design acitivity.
The Promenade -- Chap. 1. In search of authenticity: the genesis of the project -- Chap. 2. The art of the'Mal Foutu': the construction -- Chap. 3. The art of living: adjusting to Le Corbusier -- Chap. 4.'Fortuna Critica' of the Maisons Jaoul -- Conclusion. Returning the snail to its shell.
Translated from the French.
Includes bibliographical references (p. 167-170) and index.
Translated from the French.
Keywords: Le Corbusier, -- 1887-1965 -- Criticism and interpretation; Jaoul family -- Homes and haunts -- France -- Neuilly-sur-Seine.; Neuilly-sur-Seine (France) -- Buildings, structures, etc